The last quarter for sustainable environment in basketball: the carbon footprint of basketball teams in Türkiye and Lithuania - Vienažindienė, Milita; Perkumienė, Dalia; Atalay, Ahmet; Švagždiene, Biruta (Frontiers in Environmental Science, 2023)
Today, the sports industry is one of the most important sources of concern due to its negative environmental effects. Especially due to the intense competition schedule, teams and fans have to travel constantly. In this context, the aim of this study, which aims to fill the gap in the literature, is to calculate the carbon footprints of the teams in the Turkish and Lithuanian national basketball leagues based on their travels in the 2021-22 season. The research was limited to Turkey and Basketball national basketball league teams. In the study, the travel distances of the teams in both countries during the 2021-22 basketball season were used as a data set. In the study, the values used in the carbon footprint calculation of 2022 by the UK Government GHG Conversion Factors for Company Reporting and accepted as the IPCC carbon dioxide emission factor were used. While the carbon footprint, which is obtained by multiplying the emission factor directly by the distance covered by the vehicle type, is presented in tons; The average value calculated for each person was calculated in kg. In the sports sector, basketball is one of the most important sources of transportation-related carbon footprint due to its being one of the team sports and its intense competition schedule. According to the results of this research conducted specifically for Turkey and Lithuania, the total carbon footprint calculated for both countries is 53,029 tons. To make an assessment for both countries, in order to reduce travel based on sports; Arranging league calendars to include less travel, dissemination of green and clean energyusing (electric) vehicles, raising the awareness of club managers, developing environmental assessment policies specific to basketball federations, and increasing cooperation through awareness and training activities seem feasible for sustainable environment and basketball goals.